From Organizational Culture to Branch Performance: How Boundary Spanning, Team Collaboration & Resources Orchestration Drive Branch Success - Insani Astuti; Yasmine Nasution (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
The intensification of competition in the banking industry and the growing complexity of the business environment demand that bank branches go beyond routine operational functions to manage their resources adaptively and strategically. However, most prior research has focused on corporate-level performance, while studies at the branch level as a strategic operational unit remain comparatively limited. Moreover, the mechanisms through which cross-boundary organizational activities and internal factors are converted into branch performance through managerial capabilities have not been extensively tested empirically. This study examines the effects of Boundary Spanning Activity and Team Collaboration on Branch Performance, with Resource Orchestration as an intervening variable, at the level of banking branch offices. The study is grounded in the perspectives of dynamic capability and resource orchestration theory, which emphasize the importance of managerial capabilities in managing, integrating, and leveraging resources adaptively to achieve sustained performance advantage. A quantitative explanatory approach is employed with the branch office as the unit of analysis and Branch Managers as respondents; data were collected using a six-point Likert-scale questionnaire and analyzed using PLS-based SEM. Organizational Culture emerged as the strongest driver of Team Collaboration. Together with Boundary Spanning Activity, this collaboration enhances Resource Orchestration, which in turn directly impacts Branch Performance. The results confirm a serial mediation model: the internalization of an open work culture and effective cross-boundary activities convert internal capabilities into sustained operational and financial performance advantages at the branch level.